SELF - CARE BEHAVIORS AND BLOOD PRESSURE CONTROLLING OF HYPERTENSION PATIENTS, KOH SAMUI HOSPITAL, SURAT THANI PROVINCE - Meepian, Chanpen (Journal of MCU Nakhondhat, 2024)
This research aimed to study the self - care behaviors, blood pressure controlling ability, and the factors related to self - care behaviors of hypertension patients by using cross-sectional analytical research design. The sample group was 380 Thai pepole who has been diagnosed by a doctor with essential hypertension, who received treatment at the outpatient department, Koh Samui Hospital, they were able to help themselves and willing to cooperate in the study, selected by systematic random sampling. Research instruments were questionnaire and medical record form. Data were collected between 12 December 2023 and 15 January 2024 and analyzed by descriptive statistics namely number, percentage, mean, standard deviation) and Pearson’s product moment correlation. The results found that 82.1% of hypertension patients had moderate self - care behaviors, followed by good and low level at 10.8% and 7.1%, respectively. They could control blood pressure at 21.3%. In this regard, hypertensive information receiving (r = 0.284) and social support receiving (r = 0.367) were positive significantly related with self - care behaviors (p-value < 0.001) at low and medium levels, respectively. For age, duration of illness with hypertension and knowledge of hypertension and hypertensive information receiving were not related to self - care behavior. According to the results, should be promoted hypertension patients to modify the more appropriate self - care behavior, received information about high blood pressure and supported families to help care for more patients.